Persepsi Pengasuh Pondok Pesantren, Santri Jurusan Akuntansi, dan Santri Non Akuntansi, Terhadap Etika Penyusunan Laporan Keuangan Berbasis Psak Pondok Pesantren - Imam Prayogo; Atieq Amjadallah Alfie (Universitas Wahid Hasyim, 2020)
This study aims to examine the differences in perceptions between boarding school caregivers, accounting students, and non-accounting students on the ethics of preparing financial statements. Ethical indicators for the preparation of financial statements are represented in earnings management, misstatements, disclosures, cost-benefits, and responsibilities. This research was conducted at Islamic boarding schools in Central Java with a survey method of boarding school caregivers, accounting students, and non-accounting students at Islamic boarding schools in Central Java. The number of respondents in the study were 113 boarding school caretakers, 70 students majoring in accounting, and 73 non-accounting students. While the analytical tool used in this study is ANOVA for hypotheses H1, H2, H3, and H4. Anova results show that there is no difference in perceptions between the boarding school caregivers, accounting students and non-accounting students. However, there were differences in perceptions between kyai and students majoring in accounting and non-accounting students in responding to Law Number 18 of 2019 concerning Islamic Boarding Schools. There are also differences in perceptions regarding PSAK Accounting for Islamic Boarding Schools in the accounting group and non-accounting students. Therefore it can be concluded that there is no difference in perceptions of boarding school caregivers, students majoring in accounting, and non-accounting students on the ethics of preparing financial statements. Keywords: financial statement ethics, perceptions, cottage caregivers, accounting students and non-accounting students Abstrak Penelitian ini bertujuan untuk menguji tentang perbedaan persepsi antara pengasuh pondok pesantren, santri jurusan akuntansi, dan santri non akuntansi terhadap etika penyusunan laporan keuangan. Indikator etika penyusunan laporan keuangan diwakilkan pada manajemen laba, salah saji, pengungkapan, biaya-manfaat, dan tanggung jawab. Penelitian ini dilakukan pada Pondok Pesantren di Jawa Tengah dengan metode survey terhadap pengasuh pondok pesantren, santri jurusan akuntansi, dan santri non akuntansi pada Pondok Pesantren di Jawa Tengah. Jumlah responden dalam penelitian sebanyak 113 orang pengasuh pondok pesantren, 70 orang santri jurusan akuntansi, dan 73 orang santri non akuntansi. Sedangkan alat analisis yang digunakan dalam penelitian ini adalah ANOVA untuk hipotesis H1, H2, H3, dan H4. Hasil Anova menunjukkan bahwa tidak terdapat perbedaan persepsi antara kelompok pengasuh pondok pesantren, santri jurusan akuntansi dan santri non akuntansi. Namun, ditemukan perbedaan persepsi antara kyai dengan santri jurusan akuntansi serta santri non akuntansi dalam menyikapi Undang-Undang Nomor 18 Tahun 2019 tentang Pondok Pesantren. Juga terdapat perbedaan persepsi mengenai PSAK Akuntansi Pondok Pesantren pada kelompok santri jurusan akuntansi dan santri non akuntansi. Oleh karena itu dapat disimpulkan bahwa tidak terdapat perbedaan persepsi pengasuh pondok pesantren, santri jurusan akuntansi, dan santri non akuntansi terhadap etika penyusunan laporan keuangan. Kata Kunci: etika laporan keuangan, persepsi, pengasuh pondok, santri jurusan akuntansi dan santri non akuntansi